Dynamics of rotator chain with dissipative boundary: energy conduction. (March 2015) - Ke, Pu; Zheng, Zhigang
Abstract: Dynamical states of coupled rotator lattice are identified and their effects on energy conduction are explored. Globally synchronous rotation, clustered synchronous rotation and split synchronous rotation states are observed and the heat baths induced transitions between these states causes the reduction of overall energy flux. This result provides an explanation to the finite heat conductivity of coupled rotator lattice model.